Masa Depan Perusahaan Rokok di Indonesia Menggunakan Metode Altman Z-Score - Dessy Putri Andini (Politeknik Negeri Jember, 2017)
Smoking limitation implemented by government by issuing government regulation causes dilemma for cigarette companiesthemselves. Cigarette companiesare labor intensive companies which can reduce unemployment in Indonesia. However, this thing raises negative impact for the smokers themselves than passive smokers. This research aims to find out bankruptcy potential of cigarette companies listed in Bursa Efek Indonesia by using Altman Z-Score analysis because of regulation made by government. Research design used in this research is explanatory. In this research, the processed data is secondary data in form of published financial report. Research result shows that financial performance of PT. BENTOEL INTERNASIONAL INVESTAMA Tbk. in year period of 2013 was in the area of bankruptcy threatened because it suffers loss. While in 2014 â€“ 2015, it was in the area of prone to bankruptcy. It shows that regulation issued by government did not have any influence in cigarette companiesâ€™ performance generally. It was proven that only PT. BENTOEL INTERNASIONAL INVESTAMA Tbk. that was in the prone to bankruptcy area, while PT. HANJAYA MANDALA SAMPOERNA Tbk., PT. GUDANG GARAM Tbk and PT. WISMILAK INTI MAKMUR Tbk were in the healthy position.Â Keywords : Z-Score Altman, Financial Performance